COMPARATIVE ANALYSIS OF THE CONCEPT OF MONOTHEISM ON THE BASIS OF TWO DOCTRINES - Ziyoyev Alisher Abbosovich (Galaxy International Interdisciplinary Research Journal, 2021)
A comparative analysis of the concept of Tawhid and its two teachings, Ash'arism and Moturidism and evidence based on verses from the Qur’an. It also highlights the differences and interrelationships between the doctrines on this concept.